An approach to automating the implementation of applications intended for operation with compound data structures - Arushanian, O.B.; Bogomolov, N.A.; Kovalev, A.D.; Volchenskova, N.I. (Numerical Methods and Programming (Vychislitel'nye Metody i Programmirovanie), 2005)
The architecture of a basic software tool kit for automating the implementation of applications intended for interactive operation with compound data structures is described. The main concepts and software components are discussed. The work was supported by the Russian Foundation for Basic Research (04-07-90288).